Peningkatan Keterampilan Membaca melalui Kemah Literasi - Sukmawaty; Chika Utia Sari (Pedagogical Education and Review of Linguistics, 2025)
This study aims to determine how the implementation of literacy camps can improve the reading skills of fourth-grade students at SDN 245 Tole-Tole. The method used is Classroom Action Research (CAR). Data were collected through observation, tests, interviews, and documentation. The subjects of this research are the fourth-grade teacher and the fourth-grade students of SDN 245 Tole-Tole, totaling 16 students, consisting of 6 boys and 10 girls. The results of this study indicate that the reading skills of students applying literacy camps in the first cycle only achieved a score of 816 or 51%. The level of students' reading skills based on test results evaluated in the second cycle reached 1,186.1 or 74.13%, which falls into the category of very good. Thus, the reading skills of students in the second cycle experienced an improvement and achieved the category of success.